Recent Application of the Various Nanomaterials and Nanocatalysts for the Heavy Metals’ Removal from Wastewater - Khaligh, Nader Ghaffari; Johan, Mohd Rafie (World Scientific Publishing, 2018)
The pollution of water due to the release of heavy metals are particularly problematic and supplies of clean water have become a major problem worldwide. The heavy metal ions can cause toxicities and serious side effects toward human health; therefore, these metal ions should be removed from water and wastewater. A variety of strategies have been developed for efficient heavy metal removal from waters. Adsorption/ion exchange strategy play a great important role in removing heavy metal ions due to their advantages. Nanomaterials are excellent adsorbents and extensive studies have been performed to remove heavy metals from wastewater by developing and using various nanomaterials. Recent developments for the heavy metals removal by various nanomaterials, mainly including carbon-based nanomaterials, iron-based nanomaterials and photocatalytic nanomaterials in batch and flow systems are described in this review.